2020
DOI: 10.3390/cancers12113470
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of FKBP5 as Predictor of Overall Survival in Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumor with median survival of 12 months and limited effective treatments. The scope of this study was to study the relationship between blood DNA methylation (DNAm) and overall survival (OS) aiming at a noninvasive prognostic test. We investigated a cohort of 159 incident asbestos exposed MPM cases enrolled in an Italian area with high incidence of mesothelioma. Considering 12 months as a cut-off for OS, epigenome-wide association study (EWAS) revealed stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Since the methylation of TM promoter has been associated with survival and given the role of PARP1 in the methylation mechanism, this marker may be of interest for further investigation for therapeutic development. In 2019, Cugliari et al analyzed the peripheral blood of 159 MPMs and identified the CpG dinucleotide cg03546163 region associated with the gene FKBP5 as a significant marker for prognosis (205). This is very interesting as FKBP5 increases chemosensitivity to the AKT pathway, which is druggable in mesothelioma as previously described.…”
Section: Epigenetic Alterations As Promising Prognostic Biomarkersmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the methylation of TM promoter has been associated with survival and given the role of PARP1 in the methylation mechanism, this marker may be of interest for further investigation for therapeutic development. In 2019, Cugliari et al analyzed the peripheral blood of 159 MPMs and identified the CpG dinucleotide cg03546163 region associated with the gene FKBP5 as a significant marker for prognosis (205). This is very interesting as FKBP5 increases chemosensitivity to the AKT pathway, which is druggable in mesothelioma as previously described.…”
Section: Epigenetic Alterations As Promising Prognostic Biomarkersmentioning
confidence: 92%
“…In 2019, Cugliari et al. analyzed the peripheral blood of 159 MPMs and identified the CpG dinucleotide cg03546163 region associated with the gene FKBP5 as a significant marker for prognosis ( 205 ). This is very interesting as FKBP5 increases chemosensitivity to the AKT pathway, which is druggable in mesothelioma as previously described.…”
Section: Epigenetic Alterations As Promising Prognostic Biomarkersmentioning
confidence: 99%
“…Epigenetic changes have been associated with tumor progression and poor outcomes in a diverse array of tumors (28)(29)(30), and in MPM have been linked to alterations of the tumor-infiltrating immune cells. Epigenome-wide association analyses of a cohort of 159 asbestosexposed patients with MPM identified the methylation of the single-CpG marker, cg03546163, located in the 5' untranslated region of the FKBP5 gene, as associated to survival (31). This marker showed better performance compared with the traditional inflammation scores, lymphocyte-to-monocyte ratio (32), generally used as a prognostic biomarker in MPM.…”
Section: Genetic and Epigenetic Effects On The Immune Responsementioning
confidence: 99%
“…According to recent papers, both DNAm and genetic alterations may contribute to MPM tumorigenesis [ 10 , 11 , 12 , 13 , 14 , 15 ]. Whereas the genome remains consistent throughout one’s lifetime, factors like ageing, lifestyle, environmental exposures and diseases can modify DNAm.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al examined serum DNAm of nine gene-specific promoters from MM cases [ 23 ]. A more recent paper identified hypomethylation of a single CpG in FKBP5 in whole blood cells as a predictor of overall survival in MPM cases [ 13 ]. Guarrera et al evaluated methylation levels in DNA from whole blood leukocytes as potential diagnostic markers for MPM and found a differential methylation between asbestos-exposed MPM cases and controls, mainly in genes related to the immune system [ 11 ].…”
Section: Introductionmentioning
confidence: 99%